2018
DOI: 10.1111/cdev.13019
|View full text |Cite
|
Sign up to set email alerts
|

A Metatheory for Cognitive Development (or “Piaget is Dead” Revisited)

Abstract: In 1997, I argued that with the loss of Piaget's theory as an overarching guide, cognitive development had become disjointed and a new metatheory was needed to unify the field. I suggested developmental biology, particularly evolutionary theory, as a candidate. Here, I examine the increasing emphasis of biology in cognitive development research over the past 2 decades. I describe briefly the emergence of evolutionary developmental psychology and examine areas in which proximal and distal biological causation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 83 publications
3
29
0
Order By: Relevance
“…In an exploratory, post‐hoc series of analyses, we found support for Bjorklund's () observation that the neonates in our original sample tended to protrude their tongues more frequently in response to facial gesture models than to other models. Bjorklund suggested that such a tendency – while not imitation – might serve to maintain social interactions between infants and their caregivers.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In an exploratory, post‐hoc series of analyses, we found support for Bjorklund's () observation that the neonates in our original sample tended to protrude their tongues more frequently in response to facial gesture models than to other models. Bjorklund suggested that such a tendency – while not imitation – might serve to maintain social interactions between infants and their caregivers.…”
Section: Discussionsupporting
confidence: 73%
“…For each neonatal time point in the original full sample from Oostenbroek et al (), we first obtained a “face‐specific tongue protrusion score” by calculating the difference between (a) the average frequency of tongue protrusions in response to the facial gesture models (tongue protrusion, mouth opening, happy face, sad face) and (b) the average frequency of tongue protrusions in response to the seven other models. Supporting Bjorklund's () observations, a series of one‐sample t ‐tests indicated that these scores were significantly above zero at 3 weeks, t (92) = 4.52, p < .001, 6 weeks, t (100) = 3.58, p = .001 and 9 weeks of age, t (95) = 3.49, p = .001, and above zero but not significantly so at 1 week of age, t (87) = 1.88, p = .063.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations